Resistência genética do feijão (Phaseolus vulgaris L.) ao Colletotrichum lindemuthianum - Medeiros, Luis Aquiles Martins (2004)
One hundred and twenty eight genotypes of common bean (Phaseolus vulgaris L.) divided into local varieties, cultivars and lines both from meso-america and andean gene pool, were evaluated in 2003 and 2004. Several experiments were conducted at Universidade Federal de Santa Maria, State of Rio Grande do Sul, Brazil. Host genetic structure was studied based on reaction on juvenile resistance (V1/V2) to 12 physiological races of Colletotrichum lindemuthianum. Also, the relation among three phonological stages (V1/V2; R4/R5 and R5/R6) of 26 germplasm and the reaction to four races of Colletotrichum lindemuthianum was characterized. The plant reaction, virulence and resistance index were obtained from a 1 to 9 scale. The phenetic analysis was generated from virulence data considering incompatible reaction (0) and compatible reaction (1). Common bean germplasm variability was not coherent to decade of release, origin and gene pool. Higher diversity was observed among local genotypes than commercial ones. Variability of common bean lines was not related to population structure of the pathogen. The absence of Mexican genes (Co-4 and Co-5) was observed in genotypes with resistance index higher that 80%. Higher frequency of resistant genotypes was observed from 1980 to 1990. However, such result was not applied to the wide spread virulence genes. Phenetic data analysis showed that intrinsic diversity was observed among local genotypes of common bean. Specific interactions between genotypes and races were observed as growth stage evolved.